2022
DOI: 10.1002/jhet.4476
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, insecticidal activities, and molecular docking of novel pyridylpyrazolo carboxylate derivatives

Abstract: Based on our previous work, using the strategies of “scaffold hopping” and “intermediate derivatization method” (IDM), a total of 44 novel pyridylpyrazolo carboxylate derivatives were designed and synthesized. The structures of these compounds were identified by 1H NMR and 13C NMR, and the insecticidal activities of the target compounds against Plutella xylostella and Spodoptera frugiperda were tested. Compound G35 showed the best insecticidal activities against P. xylostella (LC50 = 33.65 mg/L) and S. frugipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This is evident in the compatibility of the gene expression data with molecular docking analysis (the lowest binding energy with ligands), which showed that the binding affinity between CHP and EBZ is high with SfGSTe10 and SfGSTe13 , and low with SfGSTs1 and SfGSTe2 . This result may be because the amino acids in the receptor are linked by double or triple bonds, and the docking binding affinity is high with lower binding energy [ 71 , 72 ]. Additionally, the type and position of amino acids in the active site of GSTs (the G-site and H-site) play important roles in insecticide binding affinity and catalytic functions [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in the compatibility of the gene expression data with molecular docking analysis (the lowest binding energy with ligands), which showed that the binding affinity between CHP and EBZ is high with SfGSTe10 and SfGSTe13 , and low with SfGSTs1 and SfGSTe2 . This result may be because the amino acids in the receptor are linked by double or triple bonds, and the docking binding affinity is high with lower binding energy [ 71 , 72 ]. Additionally, the type and position of amino acids in the active site of GSTs (the G-site and H-site) play important roles in insecticide binding affinity and catalytic functions [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insecticidal activity against Helicoverpa armigera . The soaking method was adopted ( Yang et al, 2022 ). After soaking a proper amount of corn leaves for 10 s, they were placed in a plastic Petri dish with filter paper and dried naturally in the shade.…”
Section: Methodsmentioning
confidence: 99%